'Every time I see him he's the worst he's ever been and the best he'll ever be': grief and sadness in children and young people who have a parent with dementia. (2nd October 2017) - Sikes, Pat; Hall, Melanie
Abstract: Research suggests that the grief experienced by the family members of persons with dementia has a distinctive nature that differentiates it from sorrow attendant on most other ill health causes. Over a variable period of time, the way in which dementia manifests in cognitive and physical changes tends to be experienced as a series of serious losses, each of which can be a source of grief leading to significant stress and emotional, mental, psychosocial and physical ill health. Research to date has focused on spouses and adult children: here we seek to add to the literature by re-presenting the grief-related perceptions and experiences of children and young people who have a parent with a young onset dementia. We draw on findings from a narrative auto/biographical investigation to describe what dementia grief was like for study participants and to make suggestions for resources and support for those in this position.